x2-10x+25=64

Move 64 to the left side of the equation by subtracting it from both sides.

x2-10x+25-64=0

Subtract 64 from 25.

x2-10x-39=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -39 and whose sum is -10.

-13,3

Write the factored form using these integers.

(x-13)(x+3)=0

(x-13)(x+3)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x-13=0

x+3=0

Set the first factor equal to 0.

x-13=0

Add 13 to both sides of the equation.

x=13

x=13

Set the next factor equal to 0.

x+3=0

Subtract 3 from both sides of the equation.

x=-3

x=-3

The final solution is all the values that make (x-13)(x+3)=0 true.

x=13,-3

Solve Using the Square Root Property x^2-10x+25=64